The Impact of Automation and Artificial Intelligence (AI) on Leadership and the Workforce - Paudel, Ram (Indonesian Journal of Banking and Financial Technology, 2024)
This inquiry explores the impact of automation and artificial intelligence (AI) on leadership and the workforce, as well as strategies for leaders to effectively navigate the transition towards a technology-focused workplace. The aim of this research is to expand current understanding by providing valuable insights into how AI and automation affect leadership and the workforce, alongside practical suggestions for managing this transformation. It is essential to recognize the potential benefits of AI and automation, such as improved efficiency and decision-making abilities, while also acknowledging concerns about potential job displacement and ethical considerations. Through a thorough examination of these issues, this study aims to equip organizations and leaders with the necessary resources to prepare for the future of work and ensure they are well-positioned for success in an increasingly technology-driven environment.